Graphene nanobubbles on TiO2 for in-operando electron spectroscopy of liquid-phase chemistry. Issue 13 (17th March 2017) - Nappini, S.; Matruglio, A.; Naumenko, D.; Dal Zilio, S.; Bondino, F.; Lazzarino, M.; Magnano, E.
Abstract : The formation of solution loaded Graphene Nanobubbles on Titania substrate allows the direct application of electron spectroscopy for the investigation of thermally induced red-ox reaction. Abstract : X-Ray Photoelectron Spectroscopy (XPS) and X-Ray Absorption Spectroscopy (XAS) provide unique knowledge on the electronic structure and chemical properties of materials. Unfortunately this information is scarce when investigating solid/liquid interfaces and chemical or photochemical reactions under ambient conditions because of the short electron inelastic mean free path (IMFP) that requires a vacuum environment, which poses serious limitation on the application of XPS and XAS to samples present in the atmosphere or in the presence of a solvent. One promising approach is the use of graphene (Gr) windows transparent to both photons and electrons. This paper proposes an innovative system based on sealed Gr nanobubbles (GNBs) on a titanium dioxide TiO2 (100) rutile single crystal filled with the solution of interest during the fabrication stage. The GNBs were successfully employed to follow in-operando the thermal-induced reduction of FeCl3 to FeCl2 in aqueous solution. The electronic states of chlorine, iron and oxygen were obtained through a combination of electron spectroscopy methods (XPS and XAS) in different phases of the process. The interaction of various components in solution with solid surfaces constituting the cell was obtained, also highlighting the formation of a covalent C–Cl bond in the Gr structure. For the easiness of GNB fabrication and straightforward extension to a large variety of solutions, we envisage a broad application of the proposed approach to investigate in detail electronic mechanisms that regulate liquid/solid electron transfer in catalytic and energy conversion related applications.